2017
DOI: 10.1096/fj.201700078r
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A regulates Akt signaling through the phospholipid fatty acid composition

Abstract: Protein kinases, including the serine/threonine kinase Akt, mediate manifold bioactivities of vitamin A, although the mechanisms behind the sustained kinase activation are diffuse. To investigate the role of cellular lipids as targetable factors in Akt signaling, we combined mass spectrometry-based lipidomics with immunologic detection of Akt (Ser473) phosphorylation. A screening campaign revealed retinol (vitamin A alcohol) and all- retinoic acid (vitamin A acid) (RA) as hits that time-dependently (≥24 h) dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Of the thirteen lyso-PL acyltransferase enzymes (20), LPCAT3 has the highest affinity for 16:0 and 18:0 lyso-PC, consistent with the specificity of reduced lyso-PC/PC (21,22). Silencing of LPCAT3 in fibroblasts has been shown to increase Akt phosphorylation (23), while incubation of the same cells with 16:0/20:4 PC decreased Akt phosphorylation due to plasma-membrane specific effects (24). Mice with a liver-specific deletion of LPCAT3 exhibit enhanced ordering of membranes (25).…”
Section: Resultsmentioning
confidence: 58%
“…Of the thirteen lyso-PL acyltransferase enzymes (20), LPCAT3 has the highest affinity for 16:0 and 18:0 lyso-PC, consistent with the specificity of reduced lyso-PC/PC (21,22). Silencing of LPCAT3 in fibroblasts has been shown to increase Akt phosphorylation (23), while incubation of the same cells with 16:0/20:4 PC decreased Akt phosphorylation due to plasma-membrane specific effects (24). Mice with a liver-specific deletion of LPCAT3 exhibit enhanced ordering of membranes (25).…”
Section: Resultsmentioning
confidence: 58%
“…The relative levels of total PC, PE, PI, PG, PS and TG are shown in Figure 6A. Various components of phospholipids are involved in the activation of AKT [33][34][35]. The Western blot experiment confirmed that Z-ligustilide+cisplatin decreased the level of phospho-AKT (p-AKT); however, PLPP1 silence reversed the expression of p-AKT in A549/DDP and H460/DDP cells (Figure 6B).…”
Section: Z-ligustilide+cisplatin Reversed Cisplatin Resistance Throug...mentioning
confidence: 84%
“…Relative levels of total PC, PE, PI, PG, PS and TG are shown in Figure 6A. Various components of phospholipids, such as PS, PI, and PC, are involved in the activation of AKT [20][21][22] which plays important roles in cell cycle progression, cell apoptosis and resistance [23]. The western blot experiment confirmed that Z-ligustilide+cisplatin decreased the level of p-AKT, however, PLPP1 silence reversed the expression of p-AKT in A549/DDP and H460/DDP cells (Figure 6B).…”
Section: Z-ligustilide+cisplatin Reversed Cisplatin Resistance Throug...mentioning
confidence: 99%